Development of decentralized controllers for industrial processes - Soh, Yeng Chai (2008)
In the project, we investigated the special properties of large-scale systems. In particular, we studied a number of problems on decentralized robust control of uncertain interconnected systems. Various decentralized robust control aglorithms are devised for different systems. Investigation of the performance of decentralized control algorithms under various conditions are carried out.